Planktonic diatoms in lotic and lentic environments in the Lago dos Tigres hydrologic system (Britânia, Goiás, Brazil) : Coscinodiscophyceae and Fragilariophyceae - Oliveira, Bárbara Dunck (2012)
Coscinodiscophyceae and Fragilariophyceae). A floristic study of Coscinodiscophyceae and Fragilariophyceae in the Lago dos Tigres hydrologic system is presented. Phytoplankton samples were collected with a plankton net (25 μm mesh) at 11 sampling stations, three in lotic areas and eight in lacustrine zones. Eleven species of Coscinodiscophyceae and eight of Fragilariophyceae were identified; descriptions, comments, their geographic distributions for the midwestern region of Brazil, type of environment (lentic/lotic), and illustrations are provided. Among the taxa found, 13 were recorded for the first time in midwestern Brazil: Aulacoseira alpigena, A. distans, A. granulata var. angustissima, A. granulata var. valida, A. muzzanensis, Discostella stelligera var. stelligera, Fragilaria capucina var. fragilarioides, F. delicatissima var. delicatissima, F. javanica, Pleurosira laevis, Staurosira acutirostrata, Staurosirella crassa, and Ulnaria ulna.